Geochemical Characteristics and Modeling of Conventional Petroleum System of Majnoon Oil Field, South Iraq. - Al Ahmed, Ahmed Askar; Al Obaidi, Qahtan Adnan (Al-Nahrain Journal of Science, 2018)
Organic geochemical analysis and model set–up to simulate the genetic relationships among 18 crude oil samples recovered from different formations and various oil fields within Amara city South Iraq, with depths approximately begin from 2167 to 4430 m, ages of marine carbonates sourced from Middle Jurassic age (Sargelu Formation) according to geochemical similarities appointed previously for this period. The levels of maturation are relatively varied for each sample from low to moderate, MJ-1, MJ-18 (Hartha Formation), MJ-3, MJ-10 (Mishrif Formation), MJ-9 (Nahr Umr Formation), MJ-15 (ZubairFormation), MJ-2, MJ-19(Nahr Umr Formation MJ- 10,MJ-11(Zubair Formation) MJ-3 (Nahr Umr Formation), Mj-3 (Sulaiy Formation), MJ-12 (two samples) Sulaiy Formation MJ-11, MJ-2 (Nahr Umr Formation), MJ-2 (Zubair Formation), MJ-11 (Sulaiy Formation )of Amara city Oil fields.These samples suggest the ages and paleoenvironments of their source rocks. The samples were collected from Upper Jurassic to Cretaceous reservoirs of 18 developed oil fields where about 15 billion barrels of recoverable oil have been reserved.The oil density varies in rather wide range, between 12.2 and 39.2 API. Twelve oil samples are ˂25 API referring to heavy oil and only oil samples attained defiantly from 25 to 35API are medium oil. Canonial Variables (CV) range attain to (- 1.89 to – 3.99) of waxy oil. According to the Tissot and Welte’s classification (1984), most of the oils can be classified as ‘‘high sulfur’’ oils/indicate that these samples are of marine origin.Stable Carbon Isotope Composition C15+ Saturate and Aromatic is relatively approximate values giving good supporting evidences for the same family which is Middle Jurassic Age (sourced from Sargelu Formation), generated within the sedimentation of the bituminous calcareous shale and Limestone in Mesopotamian basin. This basin consider as one of the most formative, potential and promising basin in the Middle East according to the typical petroleum system elements. This family was generated by marine carbonate - intrashelf sub basin source rocks, occurring in Jurassic – Cretaceous – Neogene reservoir rocks of Mesopotamian basin which are geochemically similar to the extracts from Middle –Upper Jurassic age (Sargelu Formations), yielding the majority of petroleum oil and gas fields in north and south Iraq. Petroleum system modeling in one dimension (1-D Petro Mod) was performed using Petro Mod basin modeling software which developed by Integrated Exploration System (IES) to demonstrate burial thermal history hydrocarbon generation and expulsion for Majnoon oil field so that 1-D Petro Mod was applied to Nine wells (Mj-2, Mj-3, Mj-4, Mj-8, Mj-9, Mj-11, Mj-12, Mj-15, and Mj-19) following the procedure of Pitman et al 2004.